Mesoporous Boron-Doped Carbon with Curved B4C Active Sites for Highly Efficient H2O2 Electrosynthesis in Neutral Media and Air-Supplied Environments - Choi, Jae Won; Byeon, Ayeong; Kim, Sooyeon; Hwang, Chang-Kyu; Zhang, Wenjun; Lee, Jimin; Yun, Won Chan; Paek, Sae Yane; Kim, Jin Hyeung; Jeong, Giho; Lee, Seung Yong; Moon, Joonhee; et al. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2025)
Hydrogen peroxide (H2O2) electrosynthesis via the 2e(-) oxygen reduction reaction (ORR) is considered as a cost-effective and safe alternative to the energy-intensive anthraquinone process. However, in more practical environments, namely, the use of neutral media and air-fed cathode environments, slow ORR kinetics and insufficient oxygen supply pose significant challenges to efficient H2O2 production at high current densities. In this work, mesoporous B-doped carbons with novel curved B4C active sites, synthesized via a carbon dioxide (CO2) reduction using a pore-former agent, to simultaneously achieve excellent 2e(-) ORR activity and improved mass transfer properties are introduced. Through a combination of experimental analysis and theoretical calculations, it is confirmed that the curved B4C configuration, formed by mesopores in the carbon, demonstrates superior selectivity and activity for 2e(-) ORR due to its weaker interaction with *OOH intermediates compared to planar B4C in neutral media. Moreover, the mesopores facilitate oxygen supply and suppress the hydrogen evolution reaction, achieving a Faradaic efficiency of 86.2% at 150 mA cm(-2) under air-supplied conditions, along with an impressive O-2 utilization efficiency of 93.6%. This approach will provide a route to catalyst design for efficient H2O2 electrosynthesis in a practical environment.